Monitoring extinction: defaunation, technology and the biopolitics of conservation in the Atlantic Forest, Brazil - Thomas Kiggell (Journal of Political Ecology, 2021)
Due to habitat fragmentation, Brazil's Atlantic Forest is considered one of the world's most threatened biodiversity hotspots. Much of the biome has become extinct of its largest-bodied mammals,leading some to refer it as a 'half-empty forest.' One of the ways conservation actors are responding to this crisis is by utilizing Global Positioning System(GPS), camera trapping, and remote sensing satellite imagery. Together, these tools enable the collection of data at unprecedent levels. By intensifying wildlife monitoring, it is thought that better-directed actions can be taken to avoid species extinction. Although there is a nascent body of research in political ecology examining the role of these new technologies in conservation,so far there has been little exploration of what this implies for the transformation of the governance of conservation spaces. Bringing together literatures on biopolitics of conservation and conservation technologies, this article reflects on the ways new technologies are changing the biopolitical governance of conservation in the Atlantic Forest. I argue that the increase of information flows, together with the ability to process data through models and algorithms, intensifies the capability of biopolitical governance to justify claims for new protected areas, while changing ecological subjectivities. With the increased use of remote sensing technologies, some ecologists are being distanced from the field, and are consequently having less interactions with rural communities. As pressures on biodiversity increase, this may facilitate advocacy for coercive conservation measures that have adverse impacts on local communities.